2012
DOI: 10.1007/s12016-012-8341-z
|View full text |Cite
|
Sign up to set email alerts
|

Food Allergy in Africa: Myth or Reality?

Abstract: Food allergy has been traditionally perceived as being rare in Africa. However, the prevalence of other allergic manifestations such as asthma and atopic dermatitis continue to rise in the higher-income African countries. Since the food allergy epidemic in westernized countries has lagged behind that of allergic respiratory conditions, we hypothesize that food allergy is increasing in Africa. This article systematically reviews the evidence for food allergy in Africa, obtained through searching databases inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 37 publications
2
40
0
1
Order By: Relevance
“…Kumar et al (2011) demonstrated that red beans showed cross reactivity with other legumes such as peanuts, soybean and chickpea and may induce allergic reactions in humans. Novel food allergens reported elsewhere in Africa include pineapple in Ghana, okra in Nigeria and mopane worm in Botswana (Kung et al, 2014). Similarly, chocolate can trigger headache and migraine due to consumption of increased level of tyramine, which is naturally present in cocoa products (Finocchi, & Sivori, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al (2011) demonstrated that red beans showed cross reactivity with other legumes such as peanuts, soybean and chickpea and may induce allergic reactions in humans. Novel food allergens reported elsewhere in Africa include pineapple in Ghana, okra in Nigeria and mopane worm in Botswana (Kung et al, 2014). Similarly, chocolate can trigger headache and migraine due to consumption of increased level of tyramine, which is naturally present in cocoa products (Finocchi, & Sivori, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…This study is also of value to the food industry and healthcare practitioners as the findings 9 represent a snapshot of the food allergy status in Mauritius. Limited countries in Africa had carried out research in this area (Basra et al, 2015;Gray et al, 2014;Kung et al, 2014) and there remains numerous research and development opportunities for Mauritius and other African countries.…”
Section: Insert Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The origin of sensitization to LTPs in areas of the tropics such as Ghana and the role of helminths remain unknown but provide future directions for further research. Aside from the case of Ara h 9, other novel allergens found in the tropics exist that require better characterization .…”
Section: Future Directionsmentioning
confidence: 99%
“…16 Other regionally significant food allergens can include pineapple (Ghana), okra (Nigeria), and mopane worm (Botswana). 27 Peanuts are frequently consumed in Africa, but severe allergic reactions are rare. It was assumed that there is natural clinical tolerance to peanut in African patients.…”
mentioning
confidence: 99%